IMPLEMENTAÇÃO DOS REQUISITOS DA NORMA ABNT ISO/IEC 17025 À LABORATÓRIOS: UMA PROPOSTA DE AÇÕES PARA REDUZIR A INCIDÊNCIA DE NÃO CONFORMIDADES NOS PROCESSOS DE CONCESSÃO E MANUTENÇÃO DA ACREDITAÇÃO PELA CGCRE/INMETRO. - Coutinho, Maria Angelica de Oliveira (2004)
After 1995, the search for Excellency and Quality on products and services has increased the search for Accredited Laboratories Nowadays, the Mutual Recognition Agreement (MRA) Signed by Cgcre/Inmetro, has brought some accreditation Customers from overseas. The Accreditation demands increase when Certified products and services are required, making The negotiation and free trade among those signatories of the multilateral or bilateral agreement much more easier; bringing benefits to industries and commercial users which operate in these markets. Apart from the actions taken in many accreditation quantities, it shall be necessary a strong action from the accreditation body, in order to optimize the accreditation policies already recognized by international associations such as ILAC and EA. It is very important for Cgcre/Inmetro to reduce the accreditation period, which nowadays is taking about 24 months (average). It is possible to say that wrong interpretation of NBR ISO/IEC 17025 - 2001 standard requirements and as well as of the accreditation requirements are the major difficulties found by one laboratory under accreditation process. The propose of this dissertation is to present a guidance which will assist the laboratories asking for accreditation to understand the NBR ISO/IEC 17025 2001 standard to achieve the goal, many Accreditation Assessment reports were analyzed (after 2001), where the major problems were detected and exhaustively discussed on the next 6 chapters.